Sistem Informasi SPT (Surat Perintah Tugas) Dan SPD (Surat Perjalanan Dinas) - Nor Apri Yuneta; Novita Andiyani; Ronny Mantala; Rahma Indera (P3M Politeknik Negeri Banjarmasin, 2018)
SPT (letter of assignment) and SPD (letter of official travel) are two common forms of letters made in government agencies related to the implementation of assignment and travel of civil servant (ASN). SPT and SPD are also related to the state finances used by an agency relating to the costs incurred during the official travel. The old documentary system of SPT and SPD at Balai Litbang (R & D Center) Rawa Banjarmasin is considered not effective in the process, especially in terms of making, reporting, and documentation. This research aims is to design and implement SPT and SPD Information System at Balai Litbang Rawa of Banjarmasin City. This research uses Applied Research method with system development method using SDLC (System Development Life Cycle), all data are obtained through observation and interview. The system design includes DFD, Normalization and EER Model and its implementation using Java & MySQL. The results of new application of SPT and SPD information system is able to integrate, to reduce errors, and to manage the issuance of SPT and SPD at Balai Litbang Rawa of Banjarmasin city so that the new documentary system of SPT and SPD would be better